Review of "Being Muslim: A Cultural History of Women of Color in American Islam" by Sylvia Chan-Malik (NYU Press) - Najwa Mayer (Lateral, 2020)
Sylvia Chan-Malik’s Being Muslim argues that Muslim women of color in the United States have historically engaged with Islam as concurrent rejoinders to systemic racism and those national and cultural patriarchies directed against them. Chan-Malik centers the divergent experiences and insurgent faith practices of women of color, particularly African American women, within the fundamental character of Islam in the twentieth and twenty-first century US. Through the juxtaposition of multiple methodologies—archival, discursive, affective, and oral historical—Chan-Malik follows her subjects’ complex lives rather than inserting them within expedient political or academic discourses that often subsume the intersectional politics of US women in Islam.